2020
DOI: 10.21203/rs.3.rs-22025/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk perception and behavioral response to COVID-19 in Iraqi Kurdistan Region

Abstract: Background Understanding how people perceive the risk of the coronavirus disease (COVID-19) outbreak and its impact on undertaking protective behavior can guide the public health policymakers in taking the required measures to limit the magnitude of this outbreak. This study aimed to understand the risk perception and the behavioral response of the university academics and students towards the COVID-19. Methods A self-administered online survey was conducted among the academic staff and university students in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
2
11
1
2
Order By: Relevance
“…Further, results showed that despite our expectations, adolescents relied more on credible scientific sources than social networks and their friends in critical situations. This is not in agreement with other studies’ results suggesting that academic people such as students rely highly on different online sources to obtain the latest information on the COVID-19 outbreak 25 .…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Further, results showed that despite our expectations, adolescents relied more on credible scientific sources than social networks and their friends in critical situations. This is not in agreement with other studies’ results suggesting that academic people such as students rely highly on different online sources to obtain the latest information on the COVID-19 outbreak 25 .…”
Section: Discussioncontrasting
confidence: 95%
“…This is in agreement with a study conducted in China by Wang et al that reported that despite low susceptibility, their respondents had taken precautionary measures, such as handwashing, respiratory hygiene against the outbreak of COVID-19 24 . On the contrary, the results of some studies have shown that the higher the risk perception is, the more individuals take protective measures 25 , 26 .…”
Section: Discussionmentioning
confidence: 98%
“…This fi nding is in agreement with a study conducted in Iraq, which reported respondents adopting precautionary measures including handwashing, wearing masks, wearing gloves and adherence with lockdown regulations [14]. Additionally, in a review conducted by Bish & Michie for identifying the essential attitudinal and demographics of different kinds of protective behavior, it was found that educational status is highly associated with increased chance of implementing protective behaviors [15].…”
Section: Effect Of Risk Perception On Precautionary Health Behavioral Practice Related To Covid-19supporting
confidence: 88%
“…The following formula was used to calculate our sample size n = z 2 p(1-p)/d 2 , where n is the number of samples, z is the value from the standard normal distribution for the selected confidence level (we considered z=1.96 for 95% confidence level), p = the proportion of prevalence =0.269 (26.9% was the perception for getting COVID-19), 1-p=0.731, and d= the margin of error=0.05 (considered). This information was taken from a published paper [14]. The mathematical formula delivered that 297 samples would be sufficient for our present study.…”
Section: Sample Size Determinationmentioning
confidence: 99%